Place-based perceptions, resilience and adaptation to climate change by smallholder farmers in rural South Africa - Tesfuhuney, WA; Mbeletshie, EH (International Journal of Agricultural Research, Innovation and Technology, 2021)
Unprecedented global climate change caused by human actions is becoming a challenge to agricultural systems’ ability to meet and sustain production demands for food and raw materials for the increasing world population. Climate change has not spared the district, resulting in extreme weather events such as droughts, erratic rainfalls and increasing frosty winter days within the district. Smallholder agriculture in Sub-Saharan Africa is mainly dependent on rainfed agriculture, which has increased production uncertainty due to the increasing variability of climate. This study assesses the management of adaptation and resilience strategies by smallholder farmers in Joe Gqabi District Municipality in Eastern Cape, South Africa. The study revealed a significant response to climate variability by smallholder farmers, which involved the adoption of numerous adaptation and resilience strategies. The choice of resilience and adaptation strategies among community members is influenced by a diversity of factors amongst which are; household demographic characteristics, access to information and technology, household assets endowment and farmers’ perception of climate change. Results from the study also reveal a lack of public and private institutional support to the farmers hence the lack of in-depth awareness of climate change by these farmers. Drawing on the results and conclusions, the study recommends strengthening the capacity of farmers and institutions for identifying and assessing climate change. There is an urgent need for proactive management of climate change through sustaining those attributes that are important for production (resilience) and developing new socio-ecological configurations that function effectively under new conditions (adaptation). Implementation of policy interventions that build on farmers’ existing knowledge is also critical. Int. J. Agril. Res. Innov. Tech. 10(2): 116-127, December 2020